Vitamin D status was associated with sepsis in critically ill children: A PRISMA compliant systematic review and meta-analysis. Issue 2 (15th January 2021) - Yu, Weijie; Ying, Qinlai; Zhu, Wen; Huang, Lisu; Hou, Qiuying
Abstract: Background: Sepsis leads to the high mortality in critically ill infants and children. It is still controversial whether vitamin D deficiency was associated with the incidence of sepsis. Thus we designed the systematic review and meta-analysis. Methods: The Ovid Medline, Embase, PubMed, and Cochrane library were systematically searched until April 5, 2020. The 25 hydroxyvitamin D (25-OHD) level was recorded and set 20 ng/mL as cut-off in cohort study to divide the lower and higher 25-OHD group. The odds ratio (OR) and 95% confidence intervals (CIs) were calculated for comparing the impact of vitamin D deficiency on the incidence of sepsis in critically ill children. Results: A total of 27 studies were included with 17 case-control studies and 10 cohort studies. In those case-control studies, the maternal 25-OHD level and neonatal 25-OHD level in sepsis group was significant lower than non-sepsis group ( P  < .001). The percentage of severe vitamin D deficiency was significant higher in sepsis group comparing to non-sepsis group (odds ratio [OR] = 2.66, 95% CI = 1.13–6.25, P  < .001). In those cohort studies, the incidence of sepsis in lower 25-OHD group was 30.4% comparing with 18.2% in higher 25-OHD level group. However, no statistical significant difference in terms of mechanical ventilation rate and 30-day mortality. Conclusion: We demonstrated that critically ill infants and children with sepsis could have a lower 25-OHD level and severe vitamin D deficiency comparing to those without sepsis. Future studies should focus on the association of vitamin D supplement and the occurrence of sepsis in critically ill children.